Low and High Frequency Vibration Perception Thresholds Can Improve the Diagnosis of Diabetic Neuropathy - Drechsel, Tina J.; Monteiro, Renan L.; Zippenfennig, Claudio; Ferreira, Jane S. S. P.; Milani, Thomas L.; Sacco, Isabel C. N. (Journal of clinical medicine, 2021)
Recent studies demonstrate neuropathic changes with respect to vibration sensitivity for different measurement frequencies. This study investigates the relationship between vibration perception thresholds (VPTs) at low and high frequencies at two plantar locations and diabetic peripheral neuropathy (DPN) severity in diabetes mellitus (DM) subjects with DPN. We examine differences of VPTs between participants with DM, with DPN, as well as healthy controls. The influence of anthropometric, demographic parameters, and DM duration on VPTs is studied. Thirty-three healthy control group subjects (CG: 56.3 ± 9.9 years) and 33 with DM are studied. DM participants are subdivided into DM group (DM without DPN, n = 20, 53.3 ± 15.1 years), and DPN group (DM with DPN, n = 13, 61.0 ± 14.5 years). VPTs are measured at the first metatarsal head (MTH1) and heel (30 Hz, 200 Hz), using a customized vibration exciter. Spearman and Pearson correlations are used to identify relationships between VPTs and clinical parameters. ANOVAs are calculated to compare VPTs among groups. Significant correlations are observed between DPN severity (by fuzzy scores) and VPTs at both locations and frequencies (MTH1_30 Hz vs. fuzzy: r = 0.68, p = 0.011; Heel_30 Hz vs. fuzzy: r = 0.66, p = 0.014; MTH1_200 Hz vs. fuzzy: r = 0.73, p = 0.005; Heel_200 Hz vs. fuzzy: r = 0.60, p = 0.032). VPTs in CG and DM groups are significantly smaller than the DPN group, showing higher contrasts for the 30 Hz compared to the 200 Hz measurement. The correlations between fuzzy scores and VPTs confirm the relevance of using low and high frequencies to assess a comprehensive foot sensitivity status in people with DM.